Investigation of the effectiveness of the Quick Sequential Organ Failure Assessment-Troponin scores in non- ST-elevation myocardial infarction - CANDER, BAŞAR; Cander B.; TAŞLIDERE, BAHADIR; Taşlıdere B.; SÖNMEZ, ERTAN; Sönmez E. (My University, 2023)
OBJECTIVE: A reliable predictor is needed for non-ST-elevation myocardial infarction patients with high mortality risk. The aim of this study was to assess the effectiveness of the Global Registry of Acute Coronary Events and Quick Sequential Organ Failure Assessment-Troponin (qSOFA-T) scores on in-hospital mortality rate in non-ST-elevation myocardial infarction patients. METHODS: This is an observational and retrospective study. Patients admitted to the emergency department with acute coronary syndrome were evaluated consecutively. A total of 914 patients with non-ST-elevation myocardial infarction who met inclusion criteria were included in the study. The Global Registry of Acute Coronary Events and qSOFA scores were calculated and investigated its contribution to prognostic accuracy by adding cardiac troponin I (cTnI) concentration to the qSOFA score. The threshold value of the investigated prognostic markers was calculated by receiver operating characteristic curve analysis. RESULTS: We found the in-hospital mortality rate to be 3.4%. The area under the receiver operating characteristic curve for Global Registry of Acute Coronary Events and qSOFA-T is 0.840 and 0.826, respectively. CONCLUSION: The qSOFA-T score, which can be calculated easily, quickly, and inexpensively and obtained by adding the cTnI level, had excellent discriminatory power for predicting in-hospital mortality. Difficulty in calculating the Global Registry of Acute Coronary Events score, which requires a computer, can be considered a limitation of this method. Thus, patients with a high qSOFA-T score are at an increased risk of short-term mortality. KEYWORDS: Acute coronary syndrome. Troponin I. Mortality. Non-ST elevated myocardial infarction.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE